Lighting Design Analysis in an Industrial Workshop Space: Case Study at Jakarta Creative Hub Workshop Space - Khalid Abdul Mannan (Departement of Architecture, Universitas Islam Indonesia, 2020)
The existence of light is one of the requirements for the continuity of human productivity, where human activity requires light to see. Visual comfort of workers in the industry affects their productivity levels, especially in human-based industries where humans need maximum light intensity to do work according to the level of complexity. This paper examines the lighting condition in the fashion workshop room at the Jakarta Creative Hub, to find out whether the lighting in the area is following national lighting standards for industrial areas or not. The study was carried out by a direct measurement method with a lux meter to determine the level of light intensity and simulation with software Dialux to find new lighting design alternatives. The result gathered from this study is the type and placement of light points in the Jakarta Creative Hub fashion workshop area that meets Indonesian national standards for lighting in industrial areas.Keywords: lighting, visual comfort, industry, workshop area